Government Performance Evaluation; Case Study in the Cultural Service of Kepulauan Riau Province - Ananda, Yoli; Elric, Wayne; Rusnadi, Riski (Journal Governance Society, 2024)
Government performance evaluation is a critical instrument in achieving good governance. This study aims to evaluate the performance of the Cultural Service of Kepulauan Riau Province by analyzing the achievement of strategic objectives in 2023. A descriptive quantitative approach was employed, utilizing data from the 2023 Government Performance Accountability Report (LAKIP). The analysis focused on key performance indicators, including the enhancement of cultural-based tourism destinations and the preservation of Malay culture. The findings indicate that the economic value of culture achieved 100% of its target, reflecting the successful optimization of local artists as drivers of the creative economy. Furthermore, the cultural expression value reached 95.92%, and the cultural heritage value exceeded the target at 109.28%, demonstrating the effectiveness of preservation programs for both tangible and intangible heritage. However, the evaluation identified challenges such as coordination gaps due to inconsistent government nomenclature, inadequate advocacy for cultural rights protection, and limited use of technology in cultural promotion. The study concludes that the performance of the Cultural Service of Kepulauan Riau Province in 2023 was generally strong, with significant achievements in strategic targets. Nonetheless, improvements are needed in coordination, advocacy, and technological innovation to ensure the sustainability of cultural programs. These findings are expected to serve as a foundation for more effective, efficient, and results-oriented policy development.